The White Russian Army in exile, 1920-1941 - Robinson, Paul, 1966- (Oxford historical monographs., 2002)
Paul Robinson traces the fate of the tens of thousands of soldiers of the anti-Bolshevik White Armies who fled Russia after losing the Russian civil war.